2013
DOI: 10.1016/b978-0-12-401676-7.00002-4
|View full text |Cite
|
Sign up to set email alerts
|

Aeg-1/MTDH/Lyric

Abstract: “Gain-of-function” and “loss-of-function” studies in human cancer cells and analysis of a transgenic mouse model have convincingly established that AEG-1/MTDH/LYRIC performs a seminal role in regulating proliferation, invasion, angiogenesis, metastasis, and chemoresistance, the salient defining hallmarks of cancer. These observations are strongly buttressed by clinicopathologic correlations of AEG-1/MTDH/LYRIC expression in a diverse array of cancers distinguishing AEG-1/MTDH/LYRIC as an independent biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…Subsequent studies identified AEG- 1 as a metastasis-associated gene in the mouse, called metadherin (MTDH) (8), and as a lysine-rich CEACAM1 co-isolated gene in the rat, called LYRIC (9). Recent studies in multiple cancers confirm a significant role for AEG- 1 as an oncogene (10) implicated in cancer development and progression in many organ sites (11). Based on the diverse roles of AEG- 1 in tumor progression, including transformation, growth regulation, cell survival, prevention of apoptosis, cell migration and invasion, metastasis, angiogenesis, and resistance to chemotherapy (12), this gene may provide a viable target for developing therapies for diverse cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies identified AEG- 1 as a metastasis-associated gene in the mouse, called metadherin (MTDH) (8), and as a lysine-rich CEACAM1 co-isolated gene in the rat, called LYRIC (9). Recent studies in multiple cancers confirm a significant role for AEG- 1 as an oncogene (10) implicated in cancer development and progression in many organ sites (11). Based on the diverse roles of AEG- 1 in tumor progression, including transformation, growth regulation, cell survival, prevention of apoptosis, cell migration and invasion, metastasis, angiogenesis, and resistance to chemotherapy (12), this gene may provide a viable target for developing therapies for diverse cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Astrocyte Elevated Gene-1 (AEG-1), also known as Metadherin (MTDH) and LYRIC, is an oncogene that is overexpressed in all cancers (21). AEG-1 overexpression is detected with the progression of cancer, especially in the aggressive metastatic stage, and negatively correlates with poor survival and overall adverse prognosis (21).…”
Section: Introductionmentioning
confidence: 99%
“…AEG-1 overexpression is detected with the progression of cancer, especially in the aggressive metastatic stage, and negatively correlates with poor survival and overall adverse prognosis (21). In vitro studies and investigations using nude mice xenograft and metastatic models with diverse cancer cell lines documented that AEG-1 overexpression induces an aggressive, angiogenic and metastatic phenotype whereas knockdown of AEG-1 inhibits proliferation and invasion and markedly abrogates tumor growth and metastasis (2225).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, elevated levels of MTDH have been reported in more than 20 cancer types (4), suggesting a potentially crucial and broad functionality of this gene in human cancer. Depending on the cancer type tested, recent studies using mainly cell culture systems have implicated MTDH in many cancer-related processes, including cellular proliferation, stress-induced cell death, invasion, chemoresistance and metastasis (5, 6).…”
Section: Introductionmentioning
confidence: 99%